The Presence of Television Media in Disaster Reporting to Increase the Community’s Disaster Literacy Skills - Effiati Juliana Hasibuan; Dedi Sahputra; Mazdalifah Mazdalifah (Ikatan Sarjana Komunikasi Indonesia, 2022)
Television media, on the one side, has an influence on the audience, but in reporting disasters, it is not uncommon to exploit disaster victims. On the other side, television media has the potential to make a positive contribution to disaster reporting. The purpose of this study is to determine the presence of television media in news to improve the disaster literacy skills of the community. In this study, the author uses a type of library research with descriptive analysis. Descriptive analysis method provides clear, objective, systematic, analytical and critical descriptions and information regarding the presence of television media in disaster reporting to improve the community’s disaster literacy skills. This research found that the role of television media in reporting disasters can improve people's disaster literacy skills. The presence of television media has been going well enough in reporting disasters, but it still needs to change the concept or packaging of news to avoid the impression of